Roman Gods : A Conceptual Approach (2009)
Drawing exclusively on the evidence from urban Rome up to the age of Constantine, the book analyzes the pagan, Jewish, and Christian concepts of "god" along the lines of space, time, personnel, function, iconography and ritual. Readership: All those interested in ancient religions, including Judaism and Christianity.